PENGARUH PENAMBAHAN TEPUNG KUNYIT (Curcuma domestica Valet) DALAM PAKAN TERHADAP PARAMETER HEMATOLOGI DARAH PUYUH (Coturnix-coturnix japonica) PEDAGING - Astriana Napirah (Faculty of Animal Science, Universitas Gadjah Mada, 2013)
Turmeric (Curcuma domestica Valet) is a plant that has a numerous used as feed additive belonging to phytobiotic group on broiler chicken. Turmeric contains curcumin, an active substance which is able to stimulate poultry immunity. This experiment was done to study the effect of turmeric as phytobiotic feed additive on quail blood profile. One hundred and twenty eight quails were grouped into 4 treatments with 4 replications based on completely randomized design. Diet used contain 24% crude protein and 2,900 kcal/kg metabolizable energy. The treatments were R0 (basal feed + 0% turmeric meal), R1 (basal feed + 0.1% turmeric meal), R2 (basal feed + 0.5% turmeric meal) and R3 (basal feed + 1.0% turmeric meal). Parameters measured were quail blood profile included erithrocyte and leucocyte count, haemoglobin (Hb), hematocrite, total plasma protein, lymphocyte, monocyte and neutrophil count. Data obtained during 42 days experiment was analyzed using analysis of variance based on completely randomized design and continued using least significant difference test. Turmeric meal did not affect the erythrocyte count,hematocrit, Hb and total plasma. Feeding turmeric gave a significant effect on leucocyte, neutrophil, lymphocyte andmonocyte count. Addition 1.0% of turmeric meal in quail feed showed the lowest neutrophil percentage (P<0.05), indicated antibacterial activity of curcumin contained in turmeric. The application of turmeric meal up to 1.0% in quail feed showed immunomodulatory activity by decreased neutrophil percentage and stimulated monocyte proliferation in quail blood.(Key words: Turmeric, Quail, Blood profil)